STRATEGI METAKOGNISI PEMBELAJAR ANAK DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Dyah Werdiningsih (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstrak: Tujuan penelitian ini adalah mengkaji penggunaan strategi metakognitif dalam pembelajaran bahasa Indonesia (PBI) siswa SD yang meliputi (1) intensitas penggunaan strategi metakognitif pembelajar anak; (2) interkorelasi antara strategi metakognitif dalam belajar keempat keterampilan berbahasa Indonesia; dan (3) pengaruh tingkat pendidikan terhadap penggunaan strategi metakognitif dalam belajar bahasa Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan desain deskriptif, korelasional, dan ex-post facto. Populasi penelitian ini adalah siswa SD di Kota dan Kabupaten Malang dengan teknik penyampelan cluster sampling yang berjenjang. Data dikumpulan lewat teknik keusioner dan hasilnya dianalisis dengan teknik statistik deskriptif, korelasional, dan oneway anova. Hasil penelitian ini diperoleh temuan (1) siswa SD menggunakan strategi metakognitif dengan intensitas rendah dengan rata-rata penggunaan di bawah skala 2,45; (2) penggunaan strategi metakognitif dalam belajar keempat keterampilan berbahasa Indonesia saling berinterkorelasi satu dengan lain (r= 0,980, p0,01); dan (3) terdapat pengaruh tingkat pendidikan terhadap penggunaan strategi metakognitif (sig=0.00, THE CHILDREN’S METACOGNITIVE STRATEGIES IN INDONESIAN LANGUAGE TEACHING IN ELEMENTARY SCHOOLS Abstract:This study was aimed to analyze the use of the elementary school students’ metacognitive strategies in the Indonesian Language teaching, which covered: (1) the intensity of the students’ metacognitive strategies; (2) the intercorrelation among the metacognitive strategies used in learning the four Indonesian language skills; and (3) the influence of the educational level on the use of the metacognitive strategies in learning Indonesian language. This study used the quantitative approach with the descriptive, correlational, and ex-post facto designs. The population of the study was the elementary school students in Malang municipality and regency using the multistage cluster sampling technique. The data were collected using questionnaires and analyzed using the descriptive, correlational, and one-way anova analyses. The findings showed that (1) the intensity oof the elementary school students’ use of the metacognitive strategies was low with the average of 2.45; (2) there was intercorrelation among the use of the metacognitive strategies in learning the four Indonesian language skills (r = 0.980, p0.01); and (3) there was an influence of the educational level on the use of the metacognitive strategies (sig. = 0.000, p = 0.05). Keywords: metacognitive strategies, intensity, interrcorelation, influence